Exploring Sentiment Analysis of Sustainable Finance Initiatives : A Text Mining Approach - Ririn Riani; Aam Slamet Rusydiana (Accounting and Sustainability, 2023)
To combat climate change and mitigate its negative effects, it is necessary to increase public understanding of the significance of sustainable development. The discipline of sustainable finance offers a novel opportunity to maximize financial returns by capitalizing on social progress, which constitutes a substantial competitive advantage. Moreover, sustainable finance is not only a financial development instrument for prominent proponents of sustainability, but it also represents the underlying goal of decision-makers who prioritize social responsibility. Sentiment analysis is one of the most prevalent implementations of natural language processing; therefore, this article aims to examine how the general public perceives sustainable finance. The study revealed that positive sentiment ranked highest with a percentage of 62.8%, followed by neutral sentiment with a percentage of 26.9%, and then negative sentiment with a percentage of 10.4%. The increasing popularity of environmentally favourable financial instruments has the potential to generate the necessary financial resources in the future, which are essential for financing the transition to a sustainable economy. The suggestions presented in this article are predicated on the notion that activities promoting sustainable finance are essential to the environmental, social, and economic environments. To achieve sustainable finance, the current financial system must be reconstructed and modified in accordance with sustainable development principles. In order to implement sustainable finance, it is necessary to provide support and enhancement for the adequate human resources, institutions, and new financial literacy of financial institutions.